2015
DOI: 10.1002/bdm.1864
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence, Executive Functions, and Decision Making as Predictors of Antisocial Behavior in an Adolescent Sample of Justice‐Involved Youth and a Community Comparison Group

Abstract: A clinical sample of justice-involved male adolescents and a community comparison group were compared on a battery of cognitive ability tasks (intelligence and executive functions), decision making measures, and other individual difference measures, including ratings of selfcontrol, recognition of morally debatable behaviors, and antisocial beliefs. The clinical sample displayed lower performance on cognitive abilities and decision making than the community comparison group. In particular, the clinical group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…Future studies may consider the proportionality of the samples that enable the analysis based on sociodemographic variables. It is also important to use measures complementing self-reports, such as execution tests (Li et al, 2019;Sorge et al, 2015;Yao et al, 2019), physiological, neuropsychological measures, and experiments in decision-making (van den Bos et al, 2013;van Gelder et al, 2019). Likewise, adolescent offenders' decision-making styles and the variables that affect them should be studied so that resources can be provided to foster improvements in judgment processes, well-being, mental health, and social adjustment (Fischhoff & Broomell, 2020).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies may consider the proportionality of the samples that enable the analysis based on sociodemographic variables. It is also important to use measures complementing self-reports, such as execution tests (Li et al, 2019;Sorge et al, 2015;Yao et al, 2019), physiological, neuropsychological measures, and experiments in decision-making (van den Bos et al, 2013;van Gelder et al, 2019). Likewise, adolescent offenders' decision-making styles and the variables that affect them should be studied so that resources can be provided to foster improvements in judgment processes, well-being, mental health, and social adjustment (Fischhoff & Broomell, 2020).…”
Section: Article In Pressmentioning
confidence: 99%
“…Among other aspects, analyzing decision-making implies knowledge of neurobiological mechanisms, the role of learning and memory, and understanding the purpose and analyzing the motivations, the context, and the dynamics that lie at the bottom of each decision (Altman, 2017). Methods for the study of decision-making are complementary to each other and include physiological and neuropsychological measures (van den Bos et al, 2013), self-reports, execution tests (Li et al, 2019;Sorge et al, 2015;Yao et al, 2019), and laboratory experiments (van Gelder et al, 2019). The decision-making analysis requires differentiation between situations, the level of importance of the decision, and cultural conditions.…”
mentioning
confidence: 99%
“…Researchers have found considerable support for differences in cognitive functioning between children with and without significant conduct problems; youth who commit antisocial and delinquent behaviors can have mean IQs a full standard deviation below average (Fergusson, Horwood & Ridder, 2005;Ge, Donnellan & Wenk, 2001;Kratzer & Hodgins, 1999;Lynam, Moffitt & Stouthamer-Loeber, 1993). Moreover, investigators have identified executive functioning and verbal reasoning as two areas of interest, and deficits in these domains may characterize the neuropsychological profile of early-onset antisocial behavior (Lynam & Henry, 2001;Morgan & Lilienfeld, 2000;Nordvall, Jonsson & Neely, 2017;Sorge, Skilling & Toplak, 2015).…”
Section: Risk-taking and Delinquency For Children With Developmental Delaysmentioning
confidence: 99%
“…There is strong evidence to suggest that executive function deficits are associated with challenging behaviors (Ogilvie, Stewart, Chan, & Shum, 2011), including externalizing behavior (Poland, Monks, & Tsermentseli, 2015), antisocial behavior (Sorge, Skilling, & Toplak, 2015), and aggression (Granvald & Marciszko, 2016). Executive function deficits appear to play a causal role in predicting later challenging behaviors (Hughes & Ensor, 2008; Martel et al, 2007), and interventions intended to improve children's executive function skills have had beneficial effects in reducing children's emotional and behavioral problems (Bierman et al, 2008; Domitrovich, Cortes, & Greenberg, 2007; Kam, Greenberg, & Kusche, 2004).…”
Section: Introductionmentioning
confidence: 99%